(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Low cardio respiratory fitness in young adults has emerged as an important factor for developing cardiovascular comorbidies. Increased body fat as predicted by body mass index is an additional factor for developing cardiovascular diseases. The current study was designed to find out possible association between BMI and cardio respiratory fitness among young male college students. The study population included 500 rural male college students from different colleges of Haryana state. Undergraduate, graduate, and postgraduate students who were in the adolescent age group of 18–25 years were included in the study. For assessment of Cardio respiratory endurance 9 min run/ walk test from AAHPERD health related physical fitness battery was used. For assessing BMI status of the students BMI criteria for Asia population proposed by WHO was used. There was a prevalence of overweight (29.8%), obesity I (11.6%) and obese II (0.2%) students. Most obese I students were found in the age group 17-19 years. Independent T test was used to compare the means between obese and non- obese students For descriptive analysis, mean and standard deviation values were employed. Pearson’s product-moment correlation coefficient (r) with 95% confidence (P < 0.05) was applied to determine relationship between dependent and independent variable. There was a mildly significant negative correlation (r -0.182, P < 0.01) between BMI and Cardio respiratory endurance. The value of ANOVA is found to be 4.577 which is significant at 5% level of significance, this shows that there is a significant difference in cardio respiratory endurance of students according to BMI. There was a significant difference in cardio respiratory endurance in the mean cardio respiratory endurance when compared between obese and not obese students.